Leftist Narratives in Tempo Books: Van Dijk’s Critical Discourse Analysis (CDA) Perspective: - Anas Ahmadi; Abd. Ghofur; Moh. Hafid Effendy; Nike Kusumawati; Nuria Reny Hariyati (IAIN MADURA, 2023)
The text in a narrative has hidden meanings. It is necessary to dismantle and reconstruct the new meanings using critical discourse analysis (CDA). Related to that, this study aims to explore leftist narratives in Indonesia as contained in two books published by Tempo through van Dijk’s perspective of critical discourse analysis (CDA). This study used a descriptive-interpretative method which refers to CDA. The results reveal: First, the structure of the topic’s discourse raises the subject that Tempo is on the leftist side through diction, which depicts them as religious, kind, diligent, intelligent, and having a strong sense of nationalism. Microstructurally, in terms of setting, the leftists are those who were close to Sukarno, often recited the Quran (Muslims), repeatedly discussed with the public, and defended them. While in terms of graphics, Tempo books tend to be printed in red, symbolizing communism. Second, social cognition reporting in Tempo tends to side with the PKI and criticize Suharto concerning the G30S/PKI Movement. The two books reveal the ideological conflict between communism (Russia and China) and capitalism/colonialism (the United States and its allies). Third, from the aspect of context, leftists are innocent people and are the only victims of the regime in power.